Streptococcus didelphis infection in free-ranging white-eared opossum (Didelphis albiventris) and Brazilian common opossum (Didelphis aurita): pathology, microbiologic, and genomic characterization - Daniel Oliveira dos Santos; Yasmin Gonçalves de Castro; André Duarte Vieira; Bruna Hermine de Campos; Lucas dos Reis de Souza; Nayara Ferreira de Paula; Vasco Azevedo; Bertram Brenig; Caio de Castro Cunha Figueiredo; Letícia Neves Ribeiro; Janaína Ribeiro Duarte; Vinícius Henrique Barbosa Amaral; et al. (PLoS ONE, 2026)
Marsupials of the genus Didelphis are highly adapted to urban environments and are widely distributed in the Americas. Streptococcus didelphis is a bacterium that has been isolated from, and associated with disease, in the Virginia opossum ( Didelphis virginiana ) and the white-eared opossum ( Didelphis albiventris ). This study describes pathological changes associated with S. didelphis infection in white-eared opossums ( Didelphis albiventris ) and Brazilian common opossums ( Didelphis aurita ) as well as microbiological and genomic characterization of isolates. Ten opossums underwent necropsy and had ulcerative dermatitis of probable traumatic origin had S. didelphis was isolated from cutaneous lesions (n = 16) or systemic sites (n = 4). In contrast, 34 free-ranging opossums that were captured had negative culture results for S. didelphis from nasal swabs. Other lesions in opossums naturally infected with S. didelphihs included splenitis (7/10), myocarditis (6/10), interstitial nephritis and pyelonephritis (7/10), and myositis (4/10). Most isolates were susceptible to the antimicrobial drugs tested and none of them were able to form biofilm in vitro . Whole genome analysis of six isolates revealed no resistance determinants, virulence factors or plasmids, and the isolates showed high genomic similarity.